The Utility of ICD-11 and DSM-5 Traits for Differentiating Patients With Personality Disorders From Other Clinical Groups - Pires, Rute (2021)
FUNDING This research was financially supported by the Fundação para a Ciência e a Tecnologia [Foundation for Science and Technology] through the Research Center for Psychological Science, CICPSI (UIDP/04527/2020) and the Business Research Unit, BRUIUL (UIDB/00315/2020).